Repeated Gastric Motility Measurement Affects Gastric Motility and Epigastric Symptom Sensation - Goelen, Nick; Morales, John F.; Tack, Jan; Janssen, Pieter (Frontiers in Medicine, 2020)
Background: Gastric motility is an important determinant of gastric emptying, epigastric symptom generation and intolerance to food. Motility is classically assessed directly using manometry or an intragastric balloon. These diagnostic methods are perceived as stressful and invasive, which, by itself might influence the readout of these assessments. Our hypothesis was that with repeated exposure to an invasive motility test the outcome would be different. Methods: Gastric motility was assessed with a custom-made orogastric balloon catheter in ten healthy subjects naïve to intubation. A motility index ranging from 0 (no motility) to 1 (maximum motility) was calculated in the fasted state for 3.5 hour. Symptoms were surveyed with visual analogue scales of 100 mm. Results are presented as median (interquartile range). Results: Motility index during visit 1 [0.40 (0.37-0.59)] was lower compared to visit 2 [0.50 (0.45-0.66); not significant] and 3 [0.63 (0.50-0.71); p = 0.016]. Nausea and pain scores were significantly higher during visit 1 (35 (2.8-126) and 103 (88-125) mm, respectively) compared with visit 3 [1 (2.8-26) mm (p = 0.016) and 75 (30-100) mm (p = 0.008), respectively]. No adverse events were observed. Conclusions: Repeated exposure to an invasive method to assess motility resulted in more vigorous motility and lower symptom scores. Caution is warranted when interpreting functional assessments, as prior exposure to invasive tests might confound the obtained results through habituation.